2020
DOI: 10.1039/c9ta11912d
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen vacancies on the vibrational motions of hydride ions in the oxyhydride of barium titanate

Abstract: Combined INS and DFT study on BaTiO3−xHx unravels the effect of oxygen vacancies on the vibrational dynamics of hydride ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…This can be viewed as a confirmation of the impact of the R 25 mode. This mode is very easily populated as the temperature increases, due to its very low frequency [61]. The oxygen octahedra itself remains rigid.…”
Section: Mean-square Relative Displacementmentioning
confidence: 99%
“…This can be viewed as a confirmation of the impact of the R 25 mode. This mode is very easily populated as the temperature increases, due to its very low frequency [61]. The oxygen octahedra itself remains rigid.…”
Section: Mean-square Relative Displacementmentioning
confidence: 99%
“…The quantification results reveal that BTOD NAB has a lower hydride concentration than samples reduced with CaH 2 , which is in agreement with previous studies. 17,24 The hydride shifts are tabulated in Table 1, along with the determined hydride content y. We notice that the shift becomes more negative with increasing hydride concentration, which is the first indication that the examined materials are in a bandstate.…”
Section: Comparison Of 1 H and 2 H Solid-state Nmrmentioning
confidence: 87%
“…Possibly, this ion arrangement dominates within the oxyhydride structure, therefore hydride ion diffusion occurs exclusively via the next-nearest-neighbour hopping mechanism. 17…”
Section: Hydride Conduction Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second mechanism hydride ions move through the material with the assistance of oxygen vacancies. Several investigations using complementary methods, such as isotope exchange, 5 quantum chemical calculations 15 , quasielastic neutron scattering (QENS) 16 and inelastic neutron scattering (INS) 17 have indicated that the latter mechanism most likely occurs in BaTiO 3 x H y oxyhydride and other ATiO 3 x H y pervoskites. 18,19 While the majority of the studies are in agreement on the hydride ion transport mechanism in these solids, controversies still remain on the electronic structure and the associated electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%